Diabetes mellitus and the causes of hospitalisation in people with heart failure. (10th January 2022) - Malik, Anam; Garland, Ellis; Drozd, Michael; Palin, Victoria; Giannoudi, Marilena; Straw, Sam; Jex, Nick; Walker, Andrew MN; Gierula, John; Paton, Maria; Witte, Klaus K; Kearney, Mark T; et al.
Introduction: Diabetes mellitus (DM) is associated with increased risk of hospitalisation in people with heart failure and reduced ejection fraction (HFrEF). However, little is known about the causes of these events. Methods: Prospective cohort study of 711 people with stable HFrEF. Hospitalisations were categorised by cause as: decompensated heart failure; other cardiovascular; infection or other non-cardiovascular. Rates of hospitalisation and burden of hospitalisation (percentage of follow-up time in hospital) were compared in people with and without DM. Results: After a mean follow-up of 4.0 years, 1568 hospitalisations occurred in the entire cohort. DM (present in 32% [ n =224]) was associated with a higher rate (mean 1.07 vs 0.78 per 100 patient-years; p <0.001) and burden (3.4 vs 2.2% of follow-up time; p <0.001) of hospitalisation. Cause-specific analyses revealed increased rate and burden of hospitalisation due to decompensated heart failure, other cardiovascular causes and infection in people with DM, whereas other non-cardiovascular causes were comparable. Infection made the largest contribution to the burden of hospitalisation in people with and without DM. Conclusions: In people with HFrEF, DM is associated with a greater burden of hospitalisation due to decompensated heart failure, other cardiovascular events and infection, with infection making the largest contribution.